2015
DOI: 10.1080/10298436.2015.1019498
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of IRI in short and long terms for flexible pavements: ANN and GMDH methods

Abstract: Prediction of pavement condition is one of the most important issues in pavement management systems. In this paper, capabilities of artificial neural networks (ANNs) and group method of data handling (GMDH) methods in predicting flexible pavement conditions were analysed in three levels: in 1 year, in 2 years (short term) and in the pavement life cycle (long term). For this purpose, three effective groups on pavement condition including traffic conditions, environmental changes and pavement structures were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(26 citation statements)
references
References 39 publications
1
22
0
3
Order By: Relevance
“…Üstyapıların performansını tahmin etmek için çeşitli modelleme yaklaşımları ve istatistik yöntemler kullanılmaktadır [6].…”
Section: üStyapı Performans Tahmin Modelleriunclassified
“…Üstyapıların performansını tahmin etmek için çeşitli modelleme yaklaşımları ve istatistik yöntemler kullanılmaktadır [6].…”
Section: üStyapı Performans Tahmin Modelleriunclassified
“…The RMS/PRoMMS database has been improved and updated throughout the period (2012-2016) by the JICA expert team as part of the Project "Improvement of Road Management Capability in Lao PDR" [23]. The pavement deterioration models are essential for PMS and are utilized to define various functions [8], as follows: [21,22,[25][26][27][28][29][30][31][32][33][34][35]. Some of these models were developed utilizing the Long-Term Pavement Performance (LTPP) database, whereas others were derived depending on direct field measurements or the domestic agency database.…”
Section: Introductionmentioning
confidence: 99%
“…Through reviewing the pavement performance models, it was found that the Pavement Condition Index (PCI) [8], International Roughness Index (IRI) [3,[9][10][11][12], Present Serviceability Index (PSI) [5,13], Remaining Service Life (RSL) [14], and Present Serviceability Ratio (PSR) [15] indices were more commonly used by the researchers. In terms of the modelling approach, methods such as artificial neural networks (ANN) [5,12], support vector machine (SVM) [1,11,14,15], radial basis function (RBF) [11], gene expression programming (GEP) [10], regression tree (RT) [13,16], Random Forest (RF) [3,17], and genetic programming (GP) [8] were used in the literature.…”
Section: Introductionmentioning
confidence: 99%